THE IMPACT OF “5M PLUS” HEALTH EDUCATION WITH LEAFLETS ON THE PREVENTIVE KNOWLEDGE OF DENGUE FEVER INCIDENCE IN STUDENTS OF SMPN 01 PAKISAJI PAKIS DISTRICT - Oktaviani, Olvy Oriska; AF, Swaidatul Masluhiya; Devi, Hilda Mazarina (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Dengue hemorrhagic fever (DHF) is caused by a combination of agent, environment, and host (human) factors, with humans playing a crucial role in preventing DHF through knowledge of 5 M Plus. This study aimed to assess the influence of 5M health education plus leaflets on the preventive knowledge of DHF incidents in students of SMPN 01 Pakisaji, Pakis District, Malang Regency. The study used a pre-experimental design with a one-group pre-post test. The study population comprised 212 class VII students of SMPN 01 Pakisaji, with a total sample of 138 students selected using quota sampling. The independent variable was 5M Plus health education with leaflet media, while the dependent variable was knowledge of DHF prevention. The instrument used was a knowledge questionnaire on the prevention of DHF events. Data analysis was conducted using the marginal homogeneity test, which revealed improved DHF preventive knowledge after receiving 5 M plus health education, shifting from the less category (51.4%) to the excellent category (52.9%). The study found a significant effect of 5M plus health education with leaflets on the preventive knowledge of DHF events in class VII students of SMPN 01 Pakisaji, Pakis District, Malang Regency, with a p-value of 0.000. It is anticipated that students will be able to apply 5 M Plus in both family and school environments